Three-Year Rates of Reoperation and Revision Following Mobile Versus Fixed-Bearing Total Ankle Arthroplasty: A Cohort of 302 Patients with 2 Implants of Similar Design. (17th November 2021) - Assal, M.; Kutaish, H.; Acker, A.; Hattendorf, J.; Lübbeke, A.; Crevoisier, X.
Abstract : Background: Currently, the implants utilized in total ankle arthroplasty (TAA) are divided between mobile-bearing 3-component and fixed-bearing 2-component designs. The literature evaluating the influence of this mobility difference on implant survival is sparse. The purpose of the present study was therefore to compare the short-term survival of 2 implants of similar design from the same manufacturer, surgically implanted by the same surgeons, in fixed-bearing or mobile-bearing versions. Methods: All patients were enrolled who underwent TAA with either the mobile-bearing Salto (Tornier and Integra) or the fixed-bearing Salto Talaris (Integra) in 3 centers by 2 surgeons between January 2004 and March 2018. All patients who underwent TAA from January 2004 to April 2013 received the Salto implant, and all patients who underwent TAA after November 2012 received the Salto Talaris implant. The primary outcome was time, within 3 years, to first all-cause reoperation, revision of any metal component, and revision of any component, including the polyethylene insert. Secondary outcomes included the frequency, cause, and type of reoperation. Results: A total of 302 consecutive patients were included, of whom 171 received the mobile-bearing and 131 received the fixed-bearing implant. The adjusted hazard ratio for all-cause reoperation was 1.42 (95% confidence interval [CI], 0.67 to 3.00; p = 0.36); for component revision, 3.31 (95% CI, 0.93 to 11.79; p = 0.06); and for metal component revision, 2.78 (95% CI, 0.58 to 13.33; p = 0.20). A total of 31 reoperations were performed in the mobile-bearing group compared with 14 in the fixed-bearing group (p = 0.07). More extensive reoperation procedures were performed in the mobile-bearing group. Conclusions: With the largest comparison of 2 implants of similar design from the same manufacturer, the present study supports the use of a fixed-bearing design in terms of short-term failure. We found a 3-times higher rate of revision among mobile-bearing implants compared with fixed-bearing implants at 3 years after TAA. Reoperations, including first and subsequent procedures, tended to be less common and the causes and types of reoperations less extensive among fixed-bearing implants. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.